Health Systems and Noncommunicable Diseases in the Asia-Pacific Region: A Review of the Published Literature. (March 2015) - Mannava, Priya; Abdullah, Asnawi; James, Chris; Dodd, Rebecca; Annear, Peter Leslie
Addressing the growing burden of noncommunicable diseases (NCDs) in countries of the Asia-Pacific region requires well-functioning health systems. In low- and middle-income countries (LMICs), however, health systems are generally characterized by inadequate financial and human resources, unsuitable service delivery models, and weak information systems. The aims of this review were to identify ( a ) health systems interventions being implemented to deliver NCD programs and services and their outcomes and ( b ) the health systems bottlenecks impeding access to or delivery of these programs and services in LMICs of the Asia-Pacific region. A search of 4 databases for literature published between 1990 and 2010 retrieved 36 relevant studies. For each study, information on basic characteristics, type of health systems bottleneck/intervention, and outcome was extracted, and methodological quality appraised. Health systems interventions and bottlenecks were classified as per the World Health Organization health systems building blocks framework. The review identified interventions and bottlenecks in the building blocks of service delivery, health workforce, financing, health information systems, and medical products, vaccines, and technologies. Studies, however, were heterogeneous in methodologies used, and the overall quality was generally low. There are several gaps in the evidence base around NCDs in the Asia-Pacific region that require further investigation.